2020
DOI: 10.1097/md.0000000000022884
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-to-lymphocyte ratio as a predictive index for delirium in critically ill patients

Abstract: Delirium is a neuropsychiatric syndrome commonly encountered in critically ill patients, and systemic inflammation has been strongly implicated to underlie its pathophysiology. This study aimed to investigate the predictive value of the platelet-to-lymphocyte ratio (PLR) for delirium in the intensive care unit (ICU).In this retrospective observational study, we analyzed the clinical and laboratory data of 319 ICU patients from October 2016 to December 2017. Using the Locally Weighted Scatterplot Smoothing tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…Lower preoperative PLR was ever reported to be associated with the development of POD after cardiac surgery and abdominal surgery, 6 , 8 while another study reported high PLR values in patients with delirium in the intensive care unit. 25 In our results, although patients with POD had higher postoperative PLR, perioperative PLR showed no statistically significant difference in multivariate analysis. Both platelet and lymphocyte decrease during nonspecific activation of the immune system.…”
Section: Discussioncontrasting
confidence: 48%
“…Lower preoperative PLR was ever reported to be associated with the development of POD after cardiac surgery and abdominal surgery, 6 , 8 while another study reported high PLR values in patients with delirium in the intensive care unit. 25 In our results, although patients with POD had higher postoperative PLR, perioperative PLR showed no statistically significant difference in multivariate analysis. Both platelet and lymphocyte decrease during nonspecific activation of the immune system.…”
Section: Discussioncontrasting
confidence: 48%
“…POD might possibly be predicted using biomarkers associated with inflammation 13 . It has been shown that the aberrant elevation in inflammation blood cell variables, including the neutrophil count, neutrophil‐to‐lymphocyte ratio, and platelet‐to‐lymphocyte ratio, functions as a basic indicator of inflammatory response; all of these parameters have been evaluated for their potential in POD 14–16 . However, the predictive value of inflammatory biomarkers in POD has not been investigated independently and remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A series of hematological inflammatory biomarkers, including the NLR, MLR, and PLR, have been investigated in various diseases. Previous studies reported that the NLR increases in elderly patients with delirium [ 12 ], while an increase in the PLR was associated with the development of delirium in critically ill patients [ 35 ]. Several retrospective observational studies have shown that an increased NLR is associated with the development of POD after total hip arthroplasty or head and neck free-flap reconstruction [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%